1986
DOI: 10.1104/pp.80.4.938
|View full text |Cite
|
Sign up to set email alerts
|

Proline Accumulation and the Adaptation of Cultured Plant Cells to Water Stress

Abstract: The transfer of cultured tomato cells (Lycopersicon esculentum cv VFNT-Cherry) to a low water potential environment resulted in an increased dry weight to fresh weight ratio accompanied by a rapid accumulation of proline. Proline content continued to increase as osmotic adjustment and growth occurred. The initial increase in proline concentration was accompanied by a drop in turgor. However, proline levels continued to increase with a gain in turgor during osmotic adjustment. Thus, the accumulation of proline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
1
9

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(124 citation statements)
references
References 31 publications
9
105
1
9
Order By: Relevance
“…A similar trend in proline levels is reported in tobacco (Gangaopadhyay 1997) sunflower (Hassan et al 2004). Increase in the proline accumulation on exposing calli to PEG is reported in Sorghum (Bhaskaran et al 1985) rice (Aqeel-Ahmad et al 2007) Proline accumulation under water deficit has been mainly recognized as an osmotic agent (Handa et al 1986). Selected calli exhibited osmotic adjustment in response to PEG stress through the synthesis of solutes like proline.…”
Section: Proline and Protein Accumulationmentioning
confidence: 99%
“…A similar trend in proline levels is reported in tobacco (Gangaopadhyay 1997) sunflower (Hassan et al 2004). Increase in the proline accumulation on exposing calli to PEG is reported in Sorghum (Bhaskaran et al 1985) rice (Aqeel-Ahmad et al 2007) Proline accumulation under water deficit has been mainly recognized as an osmotic agent (Handa et al 1986). Selected calli exhibited osmotic adjustment in response to PEG stress through the synthesis of solutes like proline.…”
Section: Proline and Protein Accumulationmentioning
confidence: 99%
“…Proline is generally considered as a good indicator of environmental stress in tomato (Clausen, 2005) and there are many reports describing an increase in Pro contents as a response to water or salt stress in this species (Babu et al, 2012;Ghorbanli et al, 2013;Giannakoula and Ilias, 2013;Inal, 2002;Handa et al, 1986;Nahar and Gretzmacher, 2002;Umebese et al, 2009;Yokas et al, 2008), although it should be mentioned that data specific for cherry tomatoes are rather scarce (Maggio et al, 2007;Rosales et al, 2007). What is not so clear is the possible contribution of Pro accumulation to the (relative) resistance of tomato to salinity.…”
Section: Malondialdehydementioning
confidence: 99%
“…Osmolytes are 'compatible solutes', very soluble, low-molecular-weight organic compounds that do not interfere with normal metabolism even when present at high concentrations. While toxic inorganic ions are sequestered in vacuoles, organic osmolytes accumulate predominantly in the cytoplasm, preventing or limiting cellular dehydration (Büssis and Heineke, 1998;Handa et al, 1986;Stewart and Lee, 1974). Reduction of the osmotic potential due to accumulation of osmolytes in response to stress improves the ability of the plant cells to maintain turgor pressure at low water potentials, which is essential for biological processes such as photosynthesis or cell expansion, as well as for maintaining enzymatic activities (Tyree and Jarvis, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed that proline accumulated as a response to a decrease in water potentials (Handa et al, 1986;Ober & Sharp, 1994;Bussis & Heineke, 1998) and or RWC (Rajagopal et al, 1977;Argandona & Pahlich, 1991). This response in proline content caused some osmotic adjustment (Handa et aI., 1986;Bussis & Heineke, 1998), which enabled the plant to re-acquire turgidity under water shortage.…”
Section: Discussionmentioning
confidence: 99%
“…Proline content has been reported to increase in response to a decrease in water potential (Handa et al, 1986;Ober & Sharp, 1994;Bussis & Heineke, 1998) or RWC (Rajagopal, Balasubramanian & Sinha, 1977;Argandona & Pahlich, 1991). Proline accumulation affects osmotic potential (Bussis & Heineke, 1998) and is therefore regarded as an important criterion for selecting drought tolerant crops (Singh, Aspinall & Paleg, 1972).…”
Section: Introductionmentioning
confidence: 99%